Masjid dalam Kitab Suci Negara: Pendirian Masjid dalam Peraturan Pemerintah Indonesia - Fauzul Kabir; Wahyu Trisno Aji (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
This article aims to explain how the presence of Islamic houses of worship called mosques in Indonesia in the context of Indonesia's diverse religious landscape. It highlights the role of mosques not only as centers of religious practice but also as vital community centers that foster social cohesion and spiritual development. This study emphasizes the importance of complying with government regulations regarding the establishment of religious buildings, as outlined in the Joint Ministerial Regulation (PMB) No. 9 and 8 of 2006, which aims to maintain public order in a pluralistic society. Through qualitative-descriptive methods, this study analyzes various sources to provide a comprehensive understanding of the dynamics surrounding religious practices and the legal framework that governs them in Indonesia. Ultimately, this study underlines the need for tolerance and mutual respect among different religions to promote harmony in a multicultural country.